Non-perturbative solution of the dual BBGKY hierarchy for hardsphere fluids - Gerasimenko, V.I.; Gapyak, I.V. (Доповіді НАН України, 2023)
The communication presents a rigorous description of the evolution of observables of many colliding particles. For expansions representing a solution of the Cauchy problem of the dual BBGKY hierarchy representations of their generating operators are established. Розглянуто проблему строгого опису еволюції спостережуваних плинів багатьох частинок зі зіткненнями. Для задачі Коші дуальної ієрархії ББҐКІ встановлено твірні оператори розкладів, якими зображується її розв’язок.